Estudo da obtenção de geopolímero a partir de aluminossilicato sintetizado via sol-gel - Bruna Dias de Andrade (2019)
Geopolymers have become the target of research, due to their properties as an alternative ligand for both civil construction and artificial zeolite. They are obtained by the alkaline activation of materials rich in aluminosilicates. Metakaolin, which is obtained from the kaolin calcination, is the most used raw material for the production of the geopolymer and may or may not has the composition and suitable structure for the geopolymerization. The literature describes that the geopolymer also can be obtained from aluminosilicates produced by sol-gel process. This process consists in the synthesis of chemical compounds, through the hydrolysis and condensation reactions of alkoxide precursors, with high homogeneity and high chemical purity. This work aims to study the fabrication of geopolymers from precursors synthesized by sol-gel process using them as raw materials. Silica and alumina were firstly synthesized separately and used as raw materials after physical mixing. According to the results, the conjunct production of aluminosilicates was performed. Tetraethylorthosilicate (TEOS) was used as the silica precursor, and alumina isopropoxide (IPA) and aluminum nitrate nonahydrate (ANN) as the alumina precursors. Sol-gel products and commercial metakaolin were activated with sodium hydroxide and sodium silicate to produce the geopolymers. Raw materials were characterized by gas adsorption, granulometry, thermogravimetry, X-ray diffraction and Fourier transform infrared spectroscopy. Geopolymers were also characterized by X-ray diffraction, Fourier transform infrared spectroscopy and, additionally, by density and porosity measurements via the Arquimedes method and compressive strength tests. Silica and alumina separately synthesized did not obtain satisfactory conditions to be used as raw material for the geopolymer production. However, the results of the geopolymers derived from the aluminosilicates sol-gel confirm the occurrence of alkaline activity and reach to adequate resistances at 28 days, confirming the efficiency of these materials as an alternative source in the production of geopolymers.